The Opinions of Specialists and Students Regarding the Use of Visual and Written Expression Forms in Rhinoplasty Education - Kaya, S.E.; Kemal, Ö.; Soylu Koyuncu, S. (Ondokuz Mayis Üniversitesi, 2021)
This research was conducted to investigate the contribution of visual and written expression to nasal surgery education and the preferences of usage. The research was conducted with the observation of cases in the Ear, Nose and Throat (ENT) Surgery Department of Ondokuz Mayıs University Medical Faculty. During the study, the processes of the 'closed dorsum rhinoplasty' cases were observed. The case illustrations made as a result of the observations were presented to the study population comprising 36 medical students from 3 different universities (Ondokuz Mayıs University, Hitit University, İstanbul Medeniyet University). Data were obtained concerning the sampling of the research, the specialization areas of the participants, title groups, number of participants, and the information from the Likert type responses and the nonparametric statistical findings. The results showed that although the use of illustrations was seen to be more important according to the opinion of specialists and non-specialists in the area, sole use was concluded to be insufficient. A total of 43 of 60 ENT specialists and 9 of 11 Plastic Surgery specialists preferred the use of illustrations, photographs and written expression together. Non-specialists were seen to be undecided about their responses while no significant difference was found between specialists. The preferences of the participants were determined to be illustration, photography and written expression, respectively. The results of this study indicate that the use of visual and written expression forms together when they are available is related to the quality of surgery education at a semantic level. © 2021 Ondokuz Mayis Universitesi. All rights reserved.
Keywords: Education; Medical Illustration; Nasal Surgical Procedures; Rhinoplasty